2015
DOI: 10.1016/j.bbadis.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential channel M2 contributes to neointimal hyperplasia in vascular walls

Abstract: These data suggest a critical functional role of TRPM2 in the progression of neointimal hyperplasia. The study also highlights the possibility of targeting TRPM2 as a potential therapeutic option for the treatment of occlusive vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For example, L-type Ca 2+ channels are downregulated and transient receptor potential cation (TRPC) channels are upregulated in VSMCs [156]. Of the TRPCs, the Ca 2+ -permeable TRPM2 channel was suggested to be a sensor of oxidative stress [158], and its activation by ROS leads to intracellular Ca 2+ overload inflammation [159], VSMC, migration, proliferation and apoptosis [158, 160, 161]. Another TRPC isoform, TRPC1, has also been implicated in neointimal proliferation [162].…”
Section: Recent Advancesmentioning
confidence: 99%
“…For example, L-type Ca 2+ channels are downregulated and transient receptor potential cation (TRPC) channels are upregulated in VSMCs [156]. Of the TRPCs, the Ca 2+ -permeable TRPM2 channel was suggested to be a sensor of oxidative stress [158], and its activation by ROS leads to intracellular Ca 2+ overload inflammation [159], VSMC, migration, proliferation and apoptosis [158, 160, 161]. Another TRPC isoform, TRPC1, has also been implicated in neointimal proliferation [162].…”
Section: Recent Advancesmentioning
confidence: 99%
“…These vaccine peptides can successfully attenuate atherosclerosis in mouse model 6,7 . TRPM2 is expressed in macrophages and vascular cells in vascular walls 10,11,13, 17 . Recent studies from us and others showed that TRPM2 has proinflammatory role in vascular walls, consequently promoting atherosclerotic progression 14, 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The E3 domain is a region that is hydrophilic, C-terminal to the fifth transmembrane domain (S5) and close to the predicted ion pore 16 . We have previously immunized rabbits with E3 region-based rat TRPM2 short peptide to generate a polyclonal anti-TRPM2 antibody 11, 17 . The generated antibody TM2E3 can effectively inhibit the activity of human and rat TRPM2 channels in patch clamp recording and Ca 2+ measurement study 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar increased expression of TRPC1 was also observed in the intimal layer of human vein graft samples. Thus, these channels may be novel therapeutic targets for occlusive vascular diseases [154,155].…”
Section: Vascular Stenosis After Bypass Surgery and Angioplastymentioning
confidence: 99%